An air conditioning system providing cooling, water heating and drying - Ihsan, Sany Izan; Hawlader, Mohammad Nurul Alam; Yunus, Firdaus; Mudzrin , M Irfan I (2012)
In the tropics, air conditioning is essential as the operating daily ambient temperature is high. In Malaysia and Singapore, most of the houses and apartments are air conditioned, at least one room. Every kW of electricity consumed by the air conditioner, about 4 kW is thrown into the atmosphere. Energy is available at the inlet to the condenser at about 85oC and can be utilized for useful purposes. Here, waste heat from air conditioners is utilized for water heating and drying purposes. A water condenser fitted at the exit of compressor absorbs most of the superheat and latent heat. Even a 60% recovery of this waste energy can heat 200 litres of water to 60oC within about three hours. A dryer connected at the exit of air condenser is fitted with filter to supply clean hot air to the dryer. The system reduces global warming and the payback period is less than two years.